Culture, executive functions, and academic achievement - Cho, Isu; Hosseini-Kamkar, Niki; Song, Hyun-joo; Morton, J. Bruce (Frontiers in Psychology, 2023)
Although it is well known that children of East Asian immigrants show higher academic achievement than native-born North American children, the social-cognitive determinants of this difference remain poorly understood. Given the importance of executive functions (EF) for academic achievement, and evidence that EF develops more quickly in East Asian compared to North American cultures, it is conceivable that differences in academic achievement might be rooted in EF differences between these groups. We examine this possibility by reviewing evidence of cross-cultural differences in EF development but find core concepts and findings limited in several key respects. To address these limitations, we propose a framework for relating EF, culture, and academic achievement, that draws on new theoretical ideas about the nature of EF and its relation to social context. We conclude by discussing avenues for future research on the relations between culture, executive functions, and academic achievement.